Coating Technology for Vehicle Applications - Cha, Sung Chul.; Erdemir, Ali.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book describes current, competitive coating technologies for vehicles. The authors detail how these technologies impact energy efficiency in engines and with increased use of lightweight materials and by varying coatings applications can resolve wear problems, resulting in the increased lifecycle of dies and other vehicle components.
Preface -- Energy consumption due to friction in motored vehicles and low-friction coatings to reduce it -- Diverse Coatings for Engine Parts -- Overview of DLC-coated engine components -- Coating Technologies for Automotive Engine Applications -- Customized coating systems for products with added value from development to high volume production -- Surface Treatments for Automotive Applications -- Hard Coatings and Coating Processes for the Automotive Industry -- Surface texturing for engine parts -- Coatings for Aluminum Die-casting Dies -- Coatings for Forming Dies of Advanced High-Strength Steel -- Diamond-like carbon coatings with special wettability for automotive applications -- Smart surfaces for lubrication – solid lubricants and adaptive texture -- Decorative PVD coatings on  Automotive Plastics -- Index.
Keywords: Tribology; Corrosion and anti-corrosives.; Coatings; Automotive engineering; Transportation; Energy efficiency; Tribology, Corrosion and Coatings; Automotive Engineering; Transportation; Energy Efficiency